Neonatal Sepsis: A Comprehensive Review - Charikleia Kariniotaki; Christina Thomou; Despoina Gkentzi; Eleftherios Panteris; Gabriel Dimitriou; Eleftheria Hatzidaki (Antibiotics)
Neonatal sepsis remains a significant cause of neonatal morbidity and mortality globally. At present, no clear consensus definition for sepsis in neonates exists, even though a positive blood culture is considered as the gold standard for definitive diagnosis. The accurate and timely diagnosis of sepsis in neonates presents significant difficulties, since “culture negative” or “suspected” sepsis varies widely worldwide. Antibiotic overuse and resistance are emerging problems, but on the other hand, under-recognition of sepsis and delayed antibiotic treatment could have serious or even fatal adverse outcomes in this vulnerable population. In the context of rapid recognition of sepsis and timely initiation of appropriate antibiotic therapy, various sepsis risk assessment tools have been developed, a variety of biomarkers are in clinical use or under research for future use, and new diagnostic techniques are under evaluation. In this review, we summarize the most recent data on neonatal sepsis, the utility of sepsis risk assessment tools for term and preterm infants with sepsis, and current diagnostic and preventive tools.